2008
DOI: 10.1038/embor.2008.188
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the intracellular domain of the amyloid precursor protein in complex with Fe65‐PTB2

Abstract: Cleavage of the amyloid precursor protein (APP) is a crucial event in Alzheimer disease pathogenesis that creates the amyloid-b peptide (Ab) and liberates the carboxy-terminal APP intracellular domain (AICD) into the cytosol. The interaction of the APP C terminus with the adaptor protein Fe65 mediates APP trafficking and signalling, and is thought to regulate APP processing and Ab generation. We determined the crystal structure of the AICD in complex with the C-terminal phosphotyrosine-binding (PTB) domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 30 publications
6
93
0
Order By: Relevance
“…3 A and B). Comparison of the SNX17 FERM domain/P-selectin ICD structure with the PTB domain of FE65/APP ICD complex (36), the ARH/LDLR ICD complex (5), and the Talin (F2-F3)/β1D integrin ICD complex (37) reveals that the orientation of the critical N −3 and Y 0 from the NPxY/NxxY motifs of APP, LDLR, and β1D integrin is similar to that of the analogous residues from the P-selectin ICD. Although SNX17 is only distantly related to these other proteins, it appears that the NPxY/NxxY motif of Pselectin binds SNX17 F3 via a similar mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A and B). Comparison of the SNX17 FERM domain/P-selectin ICD structure with the PTB domain of FE65/APP ICD complex (36), the ARH/LDLR ICD complex (5), and the Talin (F2-F3)/β1D integrin ICD complex (37) reveals that the orientation of the critical N −3 and Y 0 from the NPxY/NxxY motifs of APP, LDLR, and β1D integrin is similar to that of the analogous residues from the P-selectin ICD. Although SNX17 is only distantly related to these other proteins, it appears that the NPxY/NxxY motif of Pselectin binds SNX17 F3 via a similar mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Because our experiments demonstrate specific binding to known interaction partners, we conclude the array is also revealing interactions with previously unidentified cargo molecules. (36,56), the F3 subdomain of talin bound to the β1 integrin ICD (PDB ID, 3G9W), (37), and the PTB domain of ARH bound to the LRP1 ICD (PDB ID, 3SO6) (5). In each case, N −3 and Y 0 side chains from the NPxY/NxxY motif are represented in transparent green surface, and the N and C termini of the bound ICDs are indicated.…”
Section: Px-ferm Proteins Bind Promiscuously To a Large Variety Of Pumentioning
confidence: 99%
“…The phosphorylation of Thr668 results in a significant conformational change in the cytoplasmic domain of APP [115] and disrupts the interaction of APP with FE65 [94]. Further evidence for this "molecular switch" model is provided by structural analysis of AICD bound to the PTB2 domain of FE65 [32]. The binding interface of the cytoplasmic domain of APP to the PTB2 domain of FE65 consisted of two alpha-helices in addition to the typical NPTY motif.…”
Section: Phosphorylation Of App At Thr668 and Interactions With App Bmentioning
confidence: 95%
“…Structural studies have revealed that the binding interface of APP and the PTB domain of X11 involves residues within the GYENPTY motif [31]. Recently, the structures of FE65 PTB2 bound to the cytoplasmic domain of APP and of FE65L1 PTB2 bound to the APP peptide in solution were revealed by crystallography and NMR, respectively [32,33]. These studies suggest that the PTB domains of these APP binding proteins bind to the GYENPTY motif in a manner that is similar to other proteins with PTB domain, however, the presence of additional binding interfaces might allow for additional specificity.…”
Section: The Cytoplasmic Domain Of App and Its Binding Proteinsmentioning
confidence: 99%
“…Thus, the AICD swaps between two conformations, as visualized by NMR [29]. This conformational switch may in turn have crucial consequences with regard to the AICD protein interacting network, as shown for the neuronal adaptor protein Fe65 (Figure 2 and see below) [20,30]. To evaluate in as much the phosphorylation state of Thr688 controls APP processing in vivo, knockin mice were generated in which Thr668 was changed to alanine (APP TA/TA ) [31,32].…”
Section: Biology Of the Aicd: Tales Of A Tailmentioning
confidence: 99%